A review of the current state of knowledge of fossil Mantispidae (Insecta: Neuroptera) - Jepson, James E. (Zootaxa, 2015)
There are 32 individual specimens of Mantispidae (Insecta: Neuroptera) currently recorded from the fossil record, the oldest of which dates back to the Lower Jurassic. These include 19 described species (in 16 genera), 1 specimen described to genus level and 9 unnamed specimens The specimens have been assigned to the extant subfamilies Drepanicinae (4), Mantispinae (10), Symphrasinae (1), and the extinct subfamily Mesomantispinae (16), with one incertae sedis within Mantispidae. There are currently no known fossil representatives of the subfamily Calomantispinae. Mesithoninae has been removed from Mantispidae and placed back within Berothidae. The species Mesithone carnaria and M. monstruosa, however, are true mantispids and have been removed from Mesithone and placed within a new genus Karataumantispa gen. nov. in the subfamily Mesomantispinae. The current state of knowledge of the fossil record of Mantispidae is reviewed and a key to the genera of Mesomantispinae is provided.